The characterisation of a novel deubiquitinating enzyme in Escherichia coli - Channing, Debora Ruth (2010)
Although bacteria do not contain ubiquitin or ubiquitin homologues, the accurate proteolytic processing of ubiquitin precursors and ubiquitin fusion proteins in lab strains of Escherichia coli has previously been noted. We provide evidence that a novel ubiquitin-fusion processing activity in E. coli substrain RosettaTM2(DE3) represents a specific DUB activity against linear (peptide-linked) ubiquitin fusions. Fusions of ubiquitin linked to an ATP-binding cassette protein (LmrC) or to enhanced green fluorescent protein (EGFP), expressed in RosettaTM2(DE3) were cleaved precisely after the C-terminal Gly76 of ubiquitin. The use of gene knock-out showed that the source of the ubiquitin-fusion processing activity in RosettaTM2(DE3) is the ubiquitin-like protease, elaD; as specific ubiquitin-fusion processing was ablated by the inactivation of the elaD gene. Whilst this study was in progress, Catic et al. showed that elaD is present in the commensal E. coli strain K12 and intestinal pathogenic strains, but absent from extraintestinal pathogenic strains, and exhibits deubiquitinating activity in vitro against the generic substrate ubiquitin-AMC14. Our study has demonstrated that elaD not only exhibits deubiquitinating activity against linear ubiquitin fusions, but also possesses isopeptidase activity, with a preference for unanchored Lys63-linked poly-ubiquitin chains over Lys48-linked forms. GST-elaD has also been shown in this study to bind specifically to immobilised mammalian ubiquitin in pull-down assays. Thus, elaD is a bacterial enzyme which has the ability to functionally interact with the highly conserved eukaryotic ubiquitin protein and indicate that elaD may have a role in regulating host-microbe interactions.